Coronavirus disease 2019: Morphological changes in peripheral blood cells - Amin A Alamin (Iraqi Journal of Hematology, 2023)
INTRODUCTION: The impact of severe acute respiratory syndrome coronavirus 2 on global health has been considerable since its emergence. Clinical laboratories are crucial in the diagnosis, treatment, and prognosis of patients with coronavirus disease 2019 (COVID-19). The study aims to review the published literature on the abnormal morphological features found in the peripheral blood smears of patients with COVID-19. MATERIALS AND METHODS: A nonsystematic narrative review was carried out, utilizing four databases to search for publications that presented qualitative alterations in the peripheral blood cells of individuals with COVID-19. Thirty-three studies published between January 2020 and July 2022 were ultimately included in the review. RESULTS: The majority of the studies reviewed focused on qualitative changes, with peripheral blood cell shape identified as an indicator of post-COVID-19 syndrome severity. Plasmacytic cells were found to be a relatively specific marker for COVID-19, while fragmented neutrophils were identified as an extremely sensitive morphological marker. Activation of monocytes was a strong predictor of disease outcome, and platelet aggregates served as an indicator of disease progression. CONCLUSIONS: The identification of morphological abnormalities in peripheral blood cells can aid in diagnosing and prognosticating COVID-19 patients. Daily complete blood count tests in hospitalized patients are crucial for identifying numerical and morphological irregularities that indicate poor clinical outcomes and disease progression.